Classification of potential landslides using the Shuttle Radar Topography Mission imagery in the Tulis Watershed, Indonesia - Harjadi, Beny; Abdiyani, Susi; Sukartono, Inkorena G.S.; Hesthiati, Etty; Zaki, Pakhriazad Hassan; Ismail, Mohd Hasmadi (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
Tulis is one of the watersheds in the Mrica Reservoir Catchment Area in Indonesia. The Tulis Watershed has an area of 12,750 ha, which is dominated by hilly areas with areas below alluvial-colluvial. This study aimed to map the potential distribution of the landslides in the Tulis Watershed. As the Tulis Watershed has the potential for landslides, this study was conducted by using Shuttle Radar Topography Mission (SRTM) imagery year 2016. This study considered five aspects that affect landslides, namely: geological type, soil regolith depth, fault, slope, and soil texture. Areas in the Tulis Watershed were classified into five levels of landslide potential The following landslide classes and the area they cover were predicted after applying the formula: very low (0%), low (48%, 6,126 ha), moderate (51%, 6,548 ha), high (0.5%, 63 ha), and very high (0.1%, 13 ha). From the results of the level of potential landslides, several prevention and mitigation measures are recommended according to the level. For shallow landslide levels, it is recommended that relocation centers should be set up. In contrast, for those areas with very high landslide potential, it is necessary to mitigate and install Early Warning System (EWS) tools and prepare the community for adaptation.